Language Laboratory to Overcome the Barrier of Classroom English Learning: Does it Exist and Is it Used in Islamic Schools of Majene? - Nurchalis, Nur Fadillah; Ermawati, Ermawati; Sardi, Ahmed; Nursabra, Nursabra (Universitas Lancang Kuning, 2021)
A staple issue in English language teaching is the fact that individual students in formal classrooms usually have minimal opportunity to speak due to large class sizes. Recent studies have vouched language laboratories to be capable of overcoming this barrier. As far as the researchers know, no study has launched a wide investigation whether a language laboratory exists and is used to optimise the English learning in the Islamic schools in Majene, Indonesia. This research applies descriptive quantitative design, involving 22 Islamic schools in the level of junior high school. 22 English teachers that represents all the schools filled a questionnaire to provide the data. It is found that the Islamic schools at Majene do not yet have a language laboratory even though the English teachers consider it important. Its absence is influenced by the lack of support from leaders. As a result, listening practice activities are rarely carried out. English teachers only carry out practical activities in the classroom with limited tools and materials. This research illuminates a concern for policy makers in the Ministry of Religious Affairs in the field of Islamic school education and the principals to hold a language laboratory at Islamic Schools. To improve English learning activities, the existence of a language laboratory in Islamic schools is matter, so that students at Islamic schools can show their quality in foreign language mastery and compete with others.